Women in Early Modern Dutch Maritime and Colonial Worlds: Historiographical Currents and New Perspectives - Zijlstra, Suze (Early Modern Low Countries, 2025)
In the past decades, historians have taken great strides in uncovering the central position of women in Dutch maritime and colonial contexts. Emphasis is shifting, however, from a focus on maritime women in the Dutch Republic and women who were part of the colonial elites towards marginalised African, Asian, and Indigenous women in Dutch colonies and the Dutch Republic itself. Large digitisation projects are increasing the possibilities of further extracting their underrepresented perspectives from written documents, although this leads to new methodological challenges. Great care needs to be taken to not amplify biases already existing in the sources, and an awareness newly created bias by selections made when digitising is crucial. Moreover, the limitations of the written documents emphasise the importance of employing other types of sources. The future of scholarship on women in Dutch maritime and colonial worlds needs to include more object-based approaches, and quantitative patterns must be more closely explored through qualitative, interdisciplinary analysis. Various topics can be further studied to centre women in early modern colonial and maritime scholarship, including (family) networks, cross-generational patterns in family histories, strategies of survival and resistance, emotions and sexuality in empire-building, and gendered divisions in global labour and production.